Filling in the Details: A Review of Lipofilling of Radiated Tissues in the Head and Neck. Issue 3 (May 2019) - Hammond, Sarah E.; Samuels, Stuart; Thaller, Seth
Abstract : Abstract: Adipose tissue is considered by many to be an ideal filler. Fat is the model filler in that it is biocompatible, autologous tissue which typically incorporates into the host tissue with minimal complications. Along with the increasing use of fat as a soft tissue filler has come a growing interest in the development of standardized technical protocols and indications for lipofiller use. In this review, we will examine the current literature regarding lipofilling techniques, explore the potential benefits of fat grafting in radiated tissue, and discuss recent scientific advancements to optimize fat graft survival and outcomes.